2021
DOI: 10.3390/ijerph18105084
|View full text |Cite
|
Sign up to set email alerts
|

Density or Connectivity: What Are the Main Causes of the Spatial Proliferation of COVID-19 in Korea?

Abstract: COVID-19 has sparked a debate on the vulnerability of densely populated cities. Some studies argue that high-density urban centers are more vulnerable to infectious diseases due to a higher chance of infection in crowded urban environments. Other studies, however, argue that connectivity rather than population density plays a more significant role in the spread of COVID-19. While several studies have examined the role of urban density and connectivity in Europe and the U.S., few studies have been conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…It seems that controlled environments were more important than density itself. A larger, city-level analysis in South Korea found that spatial connectivity had bigger impacts on proliferating the COVID-19 pandemic than urban density [16]. Thus, people may seek controlled neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that controlled environments were more important than density itself. A larger, city-level analysis in South Korea found that spatial connectivity had bigger impacts on proliferating the COVID-19 pandemic than urban density [16]. Thus, people may seek controlled neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in the U.S. between February and April in 2020 found that a lower population density was associated with a decrease in the instantaneous reproduction number among 211 counties [15]. A study examining South Korean cities found that urban density was significantly associated with the COVID-19 infection [16].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, high network centrality enhances a range of metropolitan functions including culture and sports (Meijers et al 2016). High centrality can also lead to undesirable outcomes, for example, as highly central global cities could be susceptible to the spread of infectious diseases from distant places (Ali and Keil 2006;Jo et al 2021).…”
Section: The Importance Of Network Centralitymentioning
confidence: 99%
“…Travel mobility patterns, which are also called travel connectivity, have also been investigated in relation to COVID-19 transmission. However, the previous studies empirically identifying the impacts of travel connectivity on COVID-19 transmission may also have some limitations, in that they have limited travel mobility patterns to specific modes of travel ( Hamidi and Hamidi, 2021 ; Teller, 2021 ), or measured the degree of connectivity through social network analysis ( Murano et al, 2021 ; Jo et al, 2021 ). In a study that conducted a simulation model of vulnerability to the spread of COVID-19 in Ohio, USA, Cuadros et al (2020) employed degree centrality indicators for each travel mode calculated through social network analysis as another travel mobility and identified that the spread of infection was faster in areas with high connectivity than in areas with low connectivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Teller (2021) emphasized that travel connectivity played a decisive role in disease spread, but also noted that density and other urban factors should be considered in the spread of infectious diseases. These studies have identified urban characteristics at the county level that influence confirmed COVID-19 cases ( Hamidi et al, 2020 ; Cuadros et al, 2020 ; Ehlert, 2021 ; Jamshidi et al, 2020 ; Jo et al, 2021 ). Padmakumar and Patil (2022) investigated the impact of COVID-19 on travel mobility trends in the Indian metropolitan cities and found that such socio-economic factors, such as income, vehicle registration, and employment at the city level, had a significant impact on its change.…”
Section: Literature Reviewmentioning
confidence: 99%